Who Does the Alternate Assessment Really Assess? - Bruster, Debra (Journal of the American Academy of Special Education Professionals, 2011)
Special education teachers in Georgia are required to develop grade level tasks, reflecting grade level standards, teach the tasks and document the progress of their students with significant cognitive disabilities in the areas of math, science, literature, and social studies. The teachers must then compile the evidence of the students’ progress on the tasks into a portfolio that is graded to determine if the students (and sometimes the schools) make adequate yearly progress. This literature review will look at research concerning teachers’ perceptions of alternate assessments. This literature will attempt to prove the hypothesis that teachers perceive alternate assessments as an assessment of their ability to complete the task rather than student learning and knowledge. The literature is arranged chronologically.